On the Choice of Farm Management Practices after the Reform of the Common Agricultural Policy in 2003 - Erwin Schmid; Franz Sinabell (Austrian Institute of Economic Research (WIFO), 2004)
The Common Agricultural Policy (CAP) was fundamentally reformed in 2003. From 2005 on, farmers will receive decoupled income support payments instead of production premiums if basic standards for environment, food safety, animal health and welfare are met. Farmers will likely adjust production and management practices to the new policy framework. We describe how this reform fits into the EU strategy of making agricultural production more environmentally friendly by concentrating on financial aspects. Using an agricultural sector model for Austria, we show that the reform will further decrease agricultural outputs, reduce farm inputs, lessen nitrogen surpluses and make environmentally friendly management practices more attractive for farmers.
Keywords: Q12; Q18; Q24; Q28; 330; Common Agricultural Policy; farm management practices; agrienvironmental measures; agricultural sector model; Austria; EU-Agrarpolitik; Wirkungsanalyse; Landwirtschaft; Agrarboden; Umweltbelastung; Österreich